Effect of Dynamic Politics on The Sustainability of Local Democracy Legal Politics - Agung, Rachmat (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
This study aims to provide information regarding the influence of dynastic politics on democracy. This research strategy is a normative research strategy. Literature reviews, books, journals, papers, and relevant laws and regulations were utilized to collect data for this study. In a democratic nation, particularly Indonesia, dynastic politics have been prevalent for a long time and are a legacy of the New Order administration. In certain regions of Indonesia, dynasty politics have risen rapidly. It is believed that the practice of dynasty politics impedes the mobility of the people to participate in the phases of the General Election for Regional Heads. In addition, dynastic politics has the potential to corrupt monarchs or incumbents by bolstering the political authority and interests of their families and relatives. This is due to the lack of influence the community has on the electoral process. Observing the evolution of dynastic political practices, this is unquestionably a crucial highlight for every community. Consequently, the concept of checks and balances between the government and society is deemed essential for ensuring the continuation of the battle for leadership transitions.